The development of a strategy for vocational education and training: experiences from Montenegro - Hoppe, Melanie [Verfasser]; Burmester, Jeanette [Verfasser]; Ebben, Jan [Verfasser] (My University, 2011)
"This article addresses the problem that many countries lack a strategic orientation in reforming their vocational education and training (VET) systems, and therefore refers to the added value of a distinct VET strategy within an overall education sector strategy. To start with, the authors provide an answer to the questions 'What is strategy?' and 'What is strategy in education?' They argue that the 'resource-based view of strategy' is a suitable understanding of strategy because it has a developmental perspective and underpins the building of capacity and systems while making the most of core competences by stretching and leveraging them. Using core competences of social partners and other stakeholders is of crucial importance in VET development. By describing the process of developing a VET strategy in Montenegro, the authors provide a case study of putting strategy theory into practice. Concluding with lessons learned, they formulate recommendations." (Autorenreferat, BIBB-Doku)
Keywords: S 2.3 Berufsbildungspolitik; I 2.2.2 Osteuropa; Berufsbildungspolitik; Bildungsplanung; Strategie; Fallstudie; Montenegro